Beta-Casein Gene Polymorphism in Serbian Holstein-Friesian Cows and Its Relationship with Milk Production Traits - Marko Ristanic (Sciendo, 2020)
The most common types of beta-casein in cow’s milk are A1 and A2, which differ in one amino acid. During the gastrointestinal proteolysis of A1 beta-casein in humans this difference results in the release of beta-casomorphin-7, an opioid which may lead to severe effects on human health, causing various ailments (type-1 diabetes mellitus, ischemic heart disease, arteriosclerosis, sudden infant death syndrome, autism, schizophrenia, gastrointestinal digestive discomfort, as well as increased gastrointestinal transit time). By contrast, A2 beta-casein cannot exert these effects owing to its different composition and metabolism. Furthermore, studies have shown that it can influence milk productivity traits. Our research aimed to screen the frequency of A1 and A2 alleles of beta-casein gene in a population of Serbian Holstein-Friesian cows and to detect how the genotypes influence milk production, and milk protein and fat yields. Out of 106 animals, 13 (12.26%) were of A1A1 genotype, 58 (54.72%) of A1A2, and 35 (33.02%) of A2A2 genotype. Milk yield was significantly (P<0.01) higher in A2A2 compared to both A1A1 and A1A2 genotypes. Milk protein concentrations were significantly (P<0.01) higher in A2A2 compared to A1A2 genotype, while milk fat concentrations were significantly (P<0.01) higher in A2A2 compared to both A1A1 and A1A2 genotypes.